Modular Data Serialisation and Mobile Code - O'Leary, Ciaran (Trinity College Dublin. Department of Computer Science, 2000)
Since its creation the World Wide Web has revolutionised how we work. Academics have used it as a media to exchange research information, businesses use it to access markets previously unavailable to them and a growing percentage of society at large has been able to use it to access a global database of information. In short it has forced a rethink of the concepts of boundaries and limits. The aim of the research outlined in this dissertation is to assess the possibility of stretching the functionality of the web a little further, by developing programming languages which exploit the availability of the web as a massive data store. The objective is to use web documents, traditionally HTML documents but in the future, XML documents, as a store of data values and types for programming languages. Values created by programming languages will be saved in available data space on the web. This will in turn lead to the increased interaction between programs on the web which will be able to exchange information in the form of a XML documents. Serialisation of programming language functions and sections of code as well as values will open the door to the development of mobile programming languages. Processing of code can take place wherever sufficient resources are available on the web, or can be moved to an area where the data required is more easily accessible. Vanilla, a component based programming language development tool will be used to create prototypical programming languages that contain these capabilities.
Keywords: Computer Science